The Impact of Board Structure on Corporate Social Responsibility: A Temporal View - Galbreath, Jeremy (Wiley Interscience, 2016)
Time plays an important role in corporate social responsibility (CSR) decisions. In the context of time and the boardroom, the consideration of CSR can be affected by board structure. For example, because of considerable short-term pressures, this study posits that insiders on the board are less likely to prioritize the longer-term time horizons needed to affect CSR. Following this perspective, a hypothesis is put forth that insiders generally have temporal orientations that are more short term in nature and that they therefore have a negative effect on CSR. A study of 300 of Australia's largest firms confirmed this hypothesis. However, when inside director compensation linked to environmental and social metrics and inside director CSR training are introduced as moderating variables, their interactive effects lead to positive results: both positively moderate the negative insider-CSR relationship in environmental and social dimensions. The study contributes to a temporal view of boards of directors, as well as to corporate governance and CSR. © 2016 John Wiley & Sons, Ltd and ERP Environment.